The Role of Emotions in Establishing Meaning: Implications for Interpreting - Furmanek, Olgierda (The Journal of Specialised Translation, 2006)
Following Cronin’s (2002: 388) statement that “if we do not recognize the specific psychodynamics of orality, then our analyses of interpreting encounters will repeat assumptions that underlie depictions of unsophisticated and dissembling native”, this work intends to underline the importance of the external and internal psychological factors that influence the functioning of the interpreter, focusing on emotions and meaning. In what follows, I discuss connections between linguistic performance and emotions and present a hypothesis of its possible implications for the interpreting activity.